Encapsulating resin composition, method for producing the encapsulating resin composition, and semiconductor device
Patent Information
- Application Number
- JP2021054314
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-26
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2041-03-26
AI Technical Summary
【0009】 本発明の一態様によると、半導体素子を封止する封止材を作製するために使用でき、封止材の低弾性率化及び低線膨張係数化を実現しやすい封止用樹脂組成物、及びこの封止用樹脂組成物の製造方法、及びこの封止用樹脂組成物から作製された封止材を備える半導体装置を、提供できる。
Smart Images

Figure 0007634223000002 
Figure 0007634223000003 
Figure 0007634223000004
Abstract
Description
[Technical field]
[0001] The present invention relates to an encapsulating resin composition, a method for producing the encapsulating resin composition, and a semiconductor device, and more particularly to an encapsulating resin composition that can be used to produce an encapsulating material in a semiconductor device, a method for producing the encapsulating resin composition, and a semiconductor device including an encapsulating material containing a cured product of the encapsulating resin composition. [Background technology]
[0002] Conventionally, resin sealing has been used to seal semiconductor elements such as transistors and ICs from the viewpoints of improving productivity and reducing costs. Resin sealing is performed by molding a sealing resin composition containing, for example, an epoxy resin, a phenol-based hardener, an inorganic filler, and the like to produce a sealing material (see Patent Document 1). Patent Document 1 also discloses that the sealing resin composition contains a silicone elastomer or the like as a stress reducing agent. The elastic modulus of the sealing material is reduced by the stress reducing agent, thereby suppressing deformation and damage of the sealing material. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2018-16735 A Summary of the Invention [Problem to be solved by the invention]
[0004] In recent years, semiconductor devices used in harsh environments, such as in-vehicle semiconductor devices, are required to have high reliability capable of withstanding vibration and high temperatures. Therefore, there is a demand for encapsulants with even lower elastic modulus and linear expansion coefficient so that the encapsulants are less likely to deform or break due to impact, thermal expansion, thermal contraction, etc.
[0005] An object of the present invention is to provide an encapsulating resin composition that can be used to prepare an encapsulating material for encapsulating a semiconductor element and that can easily achieve a low elastic modulus and a low linear expansion coefficient of the encapsulating material, a method for producing the encapsulating resin composition, and a semiconductor device including an encapsulating material produced from the encapsulating resin composition. [Means for solving the problem]
[0006] The encapsulating resin composition according to one embodiment of the present invention contains a resin component (A) and an inorganic filler (B). The resin component (A) contains a reactive compound (p), a reactive compound (q) having a weight average molecular weight of 1000 or less and having a thermosetting reactivity with the reactive compound (p), and a thermoplastic polymer (r). The cured product obtained by thermally curing the resin component (A) comprises a matrix containing the thermoplastic polymer (r) and a dispersed phase containing a reaction product of the reactive compound (p) and the reactive compound (q) dispersed in the matrix.
[0007] A method for producing an encapsulating resin composition according to one embodiment of the present invention includes mixing a kneaded product (C) obtained by kneading a mixture of a reactive compound (p), a reactive compound (q) having a weight average molecular weight of 1000 or less and having thermosetting reactivity with the reactive compound (p), and a thermoplastic polymer (r), with an inorganic filler (B).
[0008] A semiconductor device according to one aspect of the present invention includes a semiconductor element and an encapsulant that encapsulates the semiconductor element. The encapsulant is a cured product of the encapsulating resin composition. Effect of the Invention
[0009] According to one aspect of the present invention, it is possible to provide an encapsulating resin composition that can be used to produce an encapsulating material for encapsulating a semiconductor element and that can easily achieve a low elastic modulus and a low linear expansion coefficient for the encapsulating material; a method for producing the encapsulating resin composition; and a semiconductor device including an encapsulating material produced from the encapsulating resin composition. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a schematic cross-sectional view of a semiconductor device according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a scanning electron microscope image of a sample made from the composition of Example 1. [Diagram 3] FIG. 3 is a scanning electron microscope image of a sample made from the composition of Example 2. [Figure 4] FIG. 4 is a scanning electron microscope image of a sample made from the composition of Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, one embodiment of the present invention will be described.
[0012] The encapsulating resin composition according to the present embodiment (hereinafter also referred to as composition (X)) contains a resin component (A) and an inorganic filler (B). The resin component (A) contains a reactive compound (p), a reactive compound (q) having a weight average molecular weight of 1000 or less and having a thermosetting reactivity with the reactive compound (p), and a thermoplastic polymer (r). The cured product obtained by thermally curing the resin component (A) comprises a matrix containing the thermoplastic polymer (r) and a dispersed phase containing a reaction product of the reactive compound (p) and the reactive compound (q) dispersed in the matrix. That is, the cured product of the resin component (A) has a so-called sea-island structure. For example, if the cross section of the cured product of the resin component (A) is not uniform and the presence of a matrix and a dispersed phase can be confirmed from an image taken with a scanning electron microscope at a magnification of 500 times or more, the cured product of the resin component (A) can be determined to have a matrix and a dispersed phase.
[0013] According to this embodiment, the cured product obtained by thermally curing the composition (X) tends to have a low elastic modulus and a low linear expansion coefficient. Therefore, when an encapsulant for a semiconductor device is produced from the composition (X), it is easy to realize a low elastic modulus and a low linear expansion coefficient of the encapsulant.
[0014] When producing the composition (X), it is preferable to prepare a kneaded product (C) by kneading the reactive compound (q) and the thermoplastic polymer (r), and then mix the reactive compound (p), the kneaded product (C), and the inorganic filler (B). When the composition (X) is produced by this method, the cured product of the resin component (A) tends to have a structure having the above-mentioned matrix and dispersed phase.
[0015] The composition of the composition (X) will be explained in more detail.
[0016] The components (constituents) contained in the composition (X) will be described.
[0017] As described above, the composition (X) contains the resin component (A) and the inorganic filler (B). The resin component (A) is the component in the composition (X) other than the inorganic filler (B).
[0018] The resin component (A) contains a reactive compound (p), a reactive compound (q), and a thermoplastic polymer (r).
[0019] The reactive compound (p) and the reactive compound (q) react and harden when heated. For example, one of the reactive compound (p) and the reactive compound (q) is a thermosetting resin and the other is a hardener.
[0020] In addition, as long as the reactive compound (p) and the reactive compound (q) react and harden by heating, the compounds contained in each of the reactive compound (p) and the reactive compound (q) are not limited to those described above.
[0021] As described above, the weight average molecular weight of the reactive compound (q) is 1000 or less. In this case, the cured product of the resin component (A) is likely to have a structure having the above-mentioned matrix and dispersed phase. In particular, when a kneaded product (C) of the reactive compound (q) and the thermoplastic polymer (r) is used in the production of the composition (X), the flow initiation temperature of the kneaded product (C) is likely to be reduced, and therefore the kneaded product (C) and the reactive compound (p) are easily kneaded together. This point will be described in detail later. In this embodiment, the weight average molecular weight is a value obtained by using a calibration curve of standard polystyrene from the measurement results obtained by gel permeation chromatography. In addition, the kneaded product (C) is measured by a temperature rise method using a high-temperature flow tester, and the temperature at which the plunger displacement changes by 1 mm from the stable value is taken as the flow initiation temperature.
[0022] The thermosetting resin contains at least one component selected from the group consisting of, for example, an epoxy resin, a benzoxazine resin, and a maleimide resin.
[0023] When the thermosetting resin contains an epoxy resin, the epoxy resin may contain any of a monomer, an oligomer, and a polymer, so long as it has two or more epoxy groups in one molecule.
[0024] The epoxy resin contains at least one component selected from the group consisting of, for example, glycidyl ether type epoxy resins, glycidyl amine type epoxy resins, glycidyl ester type epoxy resins, and olefin oxide type (alicyclic) epoxy resins. More specifically, the epoxy resin contains, for example, alkylphenol novolac type epoxy resins such as phenol novolac type epoxy resins and cresol novolac type epoxy resins; naphthol novolac type epoxy resins; phenol aralkyl type epoxy resins having a phenylene skeleton, a biphenylene skeleton, or the like; biphenyl aralkyl type epoxy resins; naphthol aralkyl type epoxy resins having a phenylene skeleton, a biphenylene skeleton, or the like; multifunctional type epoxy resins such as triphenol methane type epoxy resins and alkyl modified triphenol methane type epoxy resins; triphenyl methane type epoxy resins; tetrakisphenol ethane type epoxy resins; dicyclopentadiene type epoxy resins; The epoxy resin composition contains one or more components selected from the group consisting of anthracene-type epoxy resins; stilbene-type epoxy resins; bisphenol-type epoxy resins such as bisphenol A-type epoxy resins and bisphenol F-type epoxy resins; biphenyl-type epoxy resins; naphthalene-type epoxy resins; alicyclic epoxy resins; bromine-containing epoxy resins such as bisphenol A-type bromine-containing epoxy resins; glycidyl amine-type epoxy resins obtained by reacting polyamines such as diaminodiphenylmethane and isocyanuric acid with epichlorohydrin; and glycidyl ester-type epoxy resins obtained by reacting polybasic acids such as phthalic acid and dimer acid with epichlorohydrin.
[0025] The curing agent contains, for example, a phenolic compound. When the thermosetting resin contains at least one selected from the group consisting of epoxy resin, benzoxazine resin, and maleimide resin, if the curing agent contains a phenolic compound, the thermosetting resin and the curing agent can undergo a thermosetting reaction. Note that the curing agent is not limited to a phenolic compound as long as it undergoes a thermosetting reaction with the thermosetting resin. For example, when the thermosetting resin contains an epoxy resin, the curing agent can contain at least one component selected from, for example, a phenolic compound, an acid anhydride, an imidazole compound, and an amine compound. If the thermosetting resin contains an epoxy resin and the curing agent contains a phenolic compound, the encapsulant can have high adhesion to metal parts such as lead frames in semiconductor devices.
[0026] The phenol compound preferably contains at least one component selected from the group consisting of novolac type resins such as phenol novolac resins, cresol novolac resins, and naphthol novolac resins; phenol aralkyl resins having a phenylene skeleton or a biphenylene skeleton; aralkyl type resins such as naphthol aralkyl resins having a phenylene skeleton or a biphenylene skeleton; polyfunctional phenol resins such as triphenolmethane resins; dicyclopentadiene type phenol resins such as dicyclopentadiene type phenol novolac resins and dicyclopentadiene type naphthol novolac resins; terpene-modified phenol resins; bisphenol type resins such as bisphenol A and bisphenol F; and triazine-modified novolac resins.
[0027] The curing agent is preferably in the range of 0.5 to 1.5 equivalents relative to 1 equivalent of epoxy resin. When the curing agent is 1.5 equivalents or less, good curing properties of the composition (X) and good heat resistance and strength of the sealing material can be achieved. When the curing agent is 0.5 equivalents or more, the sealing material 62 can have particularly high adhesion to the metal part and particularly high moisture resistance. It is more preferable that the curing agent is in the range of 0.6 to 1.4 equivalents.
[0028] It is preferable that the reactive compound (q) has crystallinity. In this case, the cured product of the resin component (A) is more likely to have a structure having the above-mentioned matrix and dispersed phase. In particular, when the kneaded product (C) of the reactive compound (q) and the thermoplastic polymer (r) is used in the production of the composition (X), the flow initiation temperature of the kneaded product (C) is particularly likely to be reduced, and the fluidity of the kneaded product (C) is particularly likely to be increased.
[0029] When the reactive compound (q) has crystallinity, the melting point of the reactive compound (q) is preferably 100°C or more and 250°C or less. In this case, the reactive compound (q) preferably has an aromatic group such as a phenyl group or a naphthyl group. In this case, the cured product of the resin component (A) is particularly likely to have a structure having the above-mentioned matrix and dispersed phase, the composition (X) is particularly likely to have good moldability, and the cured product of the composition (X) is particularly likely to have a low elastic modulus and a low linear expansion coefficient. That is, when the melting point is 100°C or more, the kneaded product (C) can be easily prepared by kneading, and when the melting point is 250°C or less, the reactive compound (q) is less likely to remain unmelted in the composition (X). This can increase the homogeneity of the composition (X). The melting point is more preferably 120°C or more and 230°C or less, and even more preferably 150°C or more and 230°C or less. The melting point is the temperature at which a melting peak appears in a DSC curve obtained using a differential scanning calorimeter (DSC).
[0030] When the reactive compound (q) is a thermosetting resin and has crystallinity, the reactive compound (q) is, for example, a crystalline epoxy resin. When the reactive compound (q) is a curing agent and has crystallinity, the reactive compound (q) is, for example, a crystalline phenol compound.
[0031] In the case where the reactive compound (q) contains a crystalline epoxy resin, examples of the crystalline epoxy resin include biphenyl type epoxy resins (e.g., YX4000H and YL6121H manufactured by Mitsubishi Chemical Corporation), pseudo-anthracene skeleton-containing bifunctional epoxy resins (e.g., YX8800H and YX8800UH manufactured by Mitsubishi Chemical Corporation), thioether structure-containing bifunctional epoxy resins (e.g., YSLV-120-TE and YSLV-50-TE manufactured by Nippon Steel Chemical Co., Ltd.), bisphenol F type epoxy resins (e.g., YSLV-80XY and YSLV-70XY manufactured by Nippon Steel Chemical Co., Ltd.), anthraquinone type bifunctional epoxy resins (e.g., YDC-1312 manufactured by Nippon Steel Chemical Co., Ltd.), fluorene type bifunctional epoxy resins (e.g., OGSOL manufactured by Osaka Gas Chemical Co., Ltd.), and the like. PG-100 or PG-500), imide skeleton-containing bifunctional epoxy resins (e.g., WHR-991S manufactured by Nippon Kayaku Kogyo Co., Ltd.), and naphthalene skeleton-containing multifunctional epoxy resins (e.g., EXA470 series manufactured by DIC Corporation).
[0032] When the reactive compound (q) contains a crystalline phenol compound, examples of the crystalline phenol compound include BisP-AP and TrisP-AP manufactured by Honshu Chemical Industry Co., Ltd., and TP-VG100 manufactured by Printec Co., Ltd.
[0033] The thermoplastic polymer (r) contains at least one thermoplastic elastomer selected from the group consisting of, for example, polyester-based thermoplastic elastomers, polybutadiene-based thermoplastic elastomers, and acrylic-based thermoplastic elastomers. However, the thermoplastic polymer (r) is not limited to the above.
[0034] The weight average molecular weight of the thermoplastic polymer (r) is preferably 10,000 or more and 200,000 or less. In this case, the cured product of the resin component (A) is likely to have a structure having the above-mentioned matrix and dispersed phase, and the cured product of the composition (X) is particularly likely to have a low elastic modulus and a low linear expansion coefficient. That is, a weight average molecular weight of 10,000 or more makes it easy to form a phase separation structure, and a weight average molecular weight of 200,000 or less can suppress an increase in the viscosity of the resin component (A). The weight average molecular weight is more preferably 20,000 or more and 150,000 or less, and even more preferably 25,000 or more and 100,000 or less.
[0035] The ratio of the thermoplastic polymer (r) is preferably 20% by mass or more and 80% by mass or less with respect to the reactive compound (q). If this ratio is 20% by mass or more, the reactive compound (q) and the thermoplastic polymer (r) tend to be partially compatible with each other, and therefore, when preparing the kneaded product (C), the melting point drop phenomenon of the kneaded product (C) tends to occur easily, and therefore, when preparing the composition (X), it becomes easier to heat and knead the raw materials. In addition, if this ratio is 80% by mass or less, the increase in viscosity of the composition (X) can be suppressed. This ratio is more preferably 30% by mass or more and 70% by mass or less, and even more preferably 40% by mass or more and 60% by mass or less.
[0036] The inorganic filler (B) can contain at least one component selected from the group consisting of fused silica, such as fused spherical silica, crystalline silica, alumina, and silicon nitride. The inorganic filler (B) can reduce the linear expansion coefficient of the sealing material 62. It is preferable that the inorganic filler (B) contains fused silica. In this case, high filling property of the inorganic filler (B) in the composition (X) and high fluidity of the composition (X) during molding can be obtained. It is also preferable that the inorganic filler (B) contains at least one component selected from the group consisting of alumina, crystalline silica, and silicon nitride, and in this case, high thermal conductivity of the sealing material 62 can be obtained.
[0037] The inorganic filler (B) has an average particle size of, for example, 0.2 μm or more and 70 μm or less, preferably 0.5 μm or more and 20 μm or less. In this case, the composition (X) can have particularly good fluidity during molding. The average particle size is a volume-based median diameter calculated from the measured particle size distribution by a laser diffraction / scattering method, and can be measured using a laser diffraction / scattering particle size distribution measuring device. The inorganic filler (B) may contain two or more components with different average particle sizes in order to adjust the viscosity of the composition (X) during molding, the physical properties of the sealing material 62, and the like.
[0038] The proportion of the inorganic filler (B) is preferably 60% by mass or more and 93% by mass or less with respect to the entire composition (X). If the proportion of the inorganic filler (B) is 60% by mass or more, it is easy to particularly reduce the linear expansion coefficient of the sealing material 62. If the proportion of the inorganic filler (B) is 93% by mass or less, it is easy to ensure good fluidity of the composition (X) during molding.
[0039] Resin component (A) may contain other suitable additives than those described above within the scope of the present embodiment without impairing the effects of the present invention. For example, resin component (A) may contain at least one additive selected from the group consisting of a curing accelerator, a coupling agent, an ion trapping agent, a release agent, a flame retardant, a colorant, etc.
[0040] Examples of the curing accelerator include imidazoles such as 2-methylimidazole, 2-ethylimidazole, 2-phenylimidazole, and 2-ethyl-4-methylimidazole; cycloamidines such as 1,8-diazabicyclo[5.4.0]undecene-7, 1,5-diazabicyclo[4.3.0]nonene-5, and 5,6-dibutylamino-1,8-diazabicyclo[5.4.0]undecene-7; tertiary amines such as 2-(dimethylaminomethyl)phenol, triethylenediamine, benzyldimethylamine, triethanolamine, dimethylaminoethanol, and tris(dimethylaminomethyl)phenol; tributylphosphine, methyldiphenylphosphine, and triphenylphosphine, It is preferable that the composition contains at least one component selected from the group consisting of organic phosphines such as tris(4-methylphenyl)phosphine, diphenylphosphine, an addition reaction product of triphenylphosphine and parabenzoquinone, and phenylphosphine; tetra-substituted phosphonium and tetra-substituted borates such as tetraphenylphosphonium tetraphenylborate, tetraphenylphosphonium ethyltriphenylborate, and tetrabutylphosphonium tetrabutylborate; quaternary phosphonium salts having a counter anion other than borate; and tetraphenylboron salts such as 2-ethyl-4-methylimidazole tetraphenylborate and N-methylmorpholine tetraphenylborate.
[0041] The content of the curing accelerator is preferably 0.001 mass % or more and 0.5 mass % or less based on the entire composition (X).
[0042] The coupling agent can contribute to improving the affinity between the inorganic filler (B) and the resin component (A) and to improving the adhesion of the sealing material 62 to the metal portion.
[0043] The coupling agent may contain at least one component selected from the group consisting of silane coupling agents, titanate coupling agents, aluminum coupling agents, and aluminum / zirconium coupling agents. The silane coupling agent may contain at least one component selected from the group consisting of glycidoxysilanes such as γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; aminosilanes such as N-β(aminoethyl)-γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, and N-phenyl-γ-aminopropyltrimethoxysilane; alkylsilanes; ureidosilanes; and vinylsilanes.
[0044] The ratio of the coupling agent is preferably 0.1% by mass or more and 2.0% by mass or less based on the total amount of the inorganic filler (B) and the coupling agent, in which case the adhesion between the sealing material 62 and the metal portion is particularly high.
[0045] The production method of the composition (X) will now be described in detail.
[0046] Composition (X) can be prepared by mixing the components of composition (X) above. In this case, for example, the components are mixed in a mixer or blender until sufficiently uniform, then kneaded while being heated in a kneading machine such as a heat roll or kneader, and then cooled to room temperature.
[0047] In particular, in this embodiment, as described above, it is preferable to prepare a kneaded product (C) by kneading the reactive compound (q) and the thermoplastic polymer (r), and mix the reactive compound (p), the kneaded product (C), and the inorganic filler (B).
[0048] When kneading the reactive compound (q) and the thermoplastic polymer (r), it is preferable to mix the reactive compound (q) and the thermoplastic polymer (r) and then knead them while heating. Since the reactive compound (q) and the thermoplastic polymer (r) do not undergo a thermosetting reaction, the reactive compound (q) and the thermoplastic polymer (r) can be sufficiently kneaded without causing a curing reaction even when heated. The heating temperature during kneading is preferably equal to or higher than the higher value of the flow initiation temperature of the reactive compound (q) and the flow initiation temperature of the thermoplastic polymer (r). This heating temperature depends on the type of the reactive compound (q) and the thermoplastic polymer (r), but is, for example, 150°C or higher and 250°C or lower.
[0049] When the kneaded material (C) is prepared in this manner, the kneaded material (C) contains the reactive compound (q) having a weight average molecular weight of 1000 or less, and thus has a lower flow-start temperature and higher fluidity at the flow-start temperature or higher than that of the thermoplastic polymer (r) alone. For example, it is possible to achieve a flow-start temperature of 50°C or higher and 150°C or lower. When the reactive compound (q) has crystallinity, the fluidity of the kneaded material (C) is particularly likely to be high.
[0050] This kneaded material (C) is mixed with the components other than the kneaded material (C), i.e., the reactive compound (p) and the inorganic filler (B), and appropriate additives used as necessary. The components other than the kneaded material (C) may be mixed all at once, or may be mixed in portions.
[0051] When mixing the kneaded material (C) and the reactive compound (p), it is preferable to mix the kneaded material (C) and the reactive compound (p) and then knead them while heating. In this case, the kneaded material (C) and the reactive compound (p) are easily mixed sufficiently. The heating temperature at this time is preferably equal to or higher than the flow start temperature of the kneaded material (C) and lower than the reaction start temperature of the reactive compound (p) and the reactive compound (q). As described above, since the flow start temperature of the kneaded material (C) is lower than the flow start temperature of the thermoplastic polymer (r), even if the flow start temperature of the thermoplastic polymer (r) is higher than the reaction start temperature of the reactive compound (p) and the reactive compound (q), the reactive compound (p) and the kneaded material (C) are easily mixed sufficiently by heating and kneading. The heating temperature is appropriately set according to the circumstances, and is, for example, 90°C or higher and 150°C or lower.
[0052] Composition (X) in powder form may be produced by pulverizing composition (X) prepared by the above method. Composition (X) in tablet form may be produced by tableting powder composition (X). In addition, composition (X) may have any other suitable shape. Composition (X) according to this embodiment is preferably solid at 25°C.
[0053] As described above, the cured product obtained when the resin component (A) in the composition (X) is thermally cured comprises a matrix containing the thermoplastic polymer (r) and a dispersed phase containing the reaction product of the reactive compound (p) and the reactive compound (q) dispersed in the matrix.
[0054] The cured product of the resin component (A) can be obtained, for example, by kneading only the components of the resin component (A) while heating them to prepare a composition containing only the components of the resin component (A), and then heat-curing the composition. The cured product of the resin component (A) can also be obtained by removing the inorganic filler (B) from the composition (X) to prepare a composition containing only the resin component (A), and then heat-curing the composition. A specific example of a method for heat-curing a composition containing only the resin component (A) will be described in the Examples section. The molding conditions, such as the heating time when heat-curing the composition, may be any conditions that allow the composition to be sufficiently cured, and are preferably, for example, 130°C or more and 180°C or less. The presence of the matrix and dispersed phase can be confirmed by cutting the cured product and observing the cross section with an electron microscope.
[0055] The composition (X) having such characteristics can be produced by the composition and method described above. In this embodiment, when the composition (X) is produced by a method including mixing the reactive compound (p), the kneaded material (C) and the inorganic filler (B), particularly by kneading the reactive compound (p) and the kneaded material (C) while heating, the cured product of the resin component (A) is likely to have the above-mentioned matrix and dispersed phase. The reason for this is presumed to be as follows.
[0056] First, when the kneaded product (C) is prepared and then the kneaded product (C) is mixed with components other than the kneaded product (C), as already explained, the flow start temperature of the kneaded product (C) is lower than the flow start temperature of the thermoplastic polymer (r), so that the thermoplastic polymer (r) is easily mixed sufficiently in the composition (X). Therefore, the resin component (A) in the composition (X) is likely to form a structure in which the reactive compound (p) is dispersed in the kneaded product. When this resin component (A) is heated and cured, the reactive compound (q) in the kneaded product reacts with the reactive compound (p), consuming the reactive compound (q) in the kneaded product, thereby forming a matrix containing the thermoplastic polymer (r). In addition, the reactive compound (p) is bound to the reactive compound (q), and a reaction product between the reactive compound (p) and the reactive compound (q) is generated, which forms a dispersed phase. As a result, it is considered that the cured product of the resin component (A) has a matrix and a dispersed phase.
[0057] When the cured product of the resin component (A) has a matrix and a dispersed phase, the thermoplastic polymer (r) can be finely dispersed in the cured product of the composition (X), which is believed to enable the encapsulant made of the composition (X) to have a low elastic modulus and a low linear expansion coefficient.
[0058] The average major axis of the dispersed phase in the cured product of the resin component (A) is preferably 5 nm or more and 1000 nm or less. In this case, the reaction product of the reactive compound (p) and the reactive compound (q) and the thermoplastic polymer (r) can be particularly finely dispersed in the cured product of the composition (X), which makes it particularly easy to realize a low elastic modulus and a low linear expansion coefficient of the encapsulant. This average major axis is more preferably 500 nm or less, and even more preferably 100 nm or less.
[0059] Details of the method for confirming the presence of the matrix and the dispersed phase in the cured product of the resin component (A) and the method for determining the average major axis of the dispersed phase will be described in the Examples section.
[0060] The elastic modulus of the cured product of the composition (X) is preferably 10 GPa or less, more preferably 5 GPa or less, and even more preferably 4 GPa or less. The linear expansion coefficient of the cured product of the composition (X) is preferably 10 ppm / °C or less. The method for measuring the elastic modulus and the linear expansion coefficient will be described in detail in the Examples section. The method for evaluating the flowability of the composition (X) will be described in the Examples section.
[0061] An example of a semiconductor device 1 including an encapsulant 62 made from the composition (X) and a method for producing the same will be described.
[0062] The semiconductor device 1 is an insertion type package such as a Mini, D-pack, D2-pack, To22O, To3P, or dual in-line package (DIP), or a surface mount type package such as a quad flat package (QFP), a small outline package (SOP), a small outline J-lead package (SOJ), a plastic ball grid array (PBGA), a fine pitch ball grid array (FBGA), a wafer level package (WLP), a panel level package (PLP), a fan-out wafer level package (FO-WLP), or a fan-out panel level package (FO-PLP).
[0063] 1 shows a cross-sectional view of a semiconductor device 1 according to the present embodiment. The semiconductor device 1 includes a metal lead frame 52, a semiconductor element 50 mounted on the lead frame 52, wires 56 electrically connecting the semiconductor element 50 and the lead frame 52, and an encapsulant 62 encapsulating the semiconductor element 50.
[0064] In this embodiment, the lead frame 52 includes a die pad 58, an inner lead 521, and an outer lead 522. The lead frame 52 is made of, for example, copper or an iron alloy such as 42 alloy. The lead frame 52 preferably includes a main body 53 made of copper or an iron alloy such as 42 alloy, and a plating layer 54 covering the main body 53. In this case, corrosion of the lead frame 52 is suppressed. The plating layer 54 preferably includes at least one component of silver, nickel, and palladium. The plating layer 54 may include only one metal of silver, nickel, and palladium, or may include an alloy including at least one metal of silver, nickel, and palladium. The plating layer 54 may have a laminated structure, and specifically may have a laminated structure including, for example, a palladium layer, a nickel layer, and a gold layer. The thickness of the plating layer 54 is, for example, within a range of 1 to 20 μm, but is not particularly limited thereto.
[0065] The semiconductor element 50 is fixed onto the die pad 58 of the lead frame 52 with an appropriate die bonding material 60. In this way, the semiconductor element 50 is mounted on the lead frame 52. The semiconductor element 50 is, for example, an integrated circuit, a large scale integrated circuit, a transistor, a thyristor, a diode, or a solid-state imaging element. The semiconductor element 50 may be a new power device such as SiC or GaN.
[0066] Next, the semiconductor element 50 and the inner lead 521 of the lead frame 52 are connected by a wire 56. The wire 56 may be made of gold, or may contain at least one of copper and silver. For example, the wire 56 may be made of silver or copper. When the wire 56 contains at least one of copper and silver, the wire 56 may be coated with a thin film of a metal such as palladium.
[0067] Next, the composition (X) is molded to form an encapsulant 62 that encapsulates the semiconductor element 50. The encapsulant 62 also encapsulates the wires 56. The encapsulant 62 also encapsulates the die pad 58 and the inner lead 521, and therefore the encapsulant 62 is in contact with the lead frame 52, and in the case where the lead frame 52 has a plating layer 54, the encapsulant 62 is in contact with the plating layer 54.
[0068] The encapsulating composition is preferably molded by a pressure molding method to produce the encapsulant 62. The pressure molding method is, for example, an injection molding method, a transfer molding method, or a compression molding method.
[0069] The conditions for molding the encapsulating composition by the pressure molding method are appropriately set according to the composition of the encapsulating composition. For example, when the encapsulating composition contains an epoxy resin as a thermosetting resin and a phenol compound as a curing agent, the molding pressure when molding the composition (X) by the pressure molding method is, for example, 3.0 MPa or more, and the molding temperature is 120°C or more.
[0070] In particular, in the case of the transfer molding method, the injection pressure of the composition (X) into the mold is, for example, 3 MPa or more, and preferably 4 MPa or more and 710 MPa or less. The heating temperature (mold temperature) is preferably 120° C. or more, and more preferably 160° C. or more and 190° C. or less. The heating time is, for example, 30 seconds or more and 300 seconds or less, and more preferably 60 seconds or more and 180 seconds or less.
[0071] In the transfer molding method, it is preferable to prepare the encapsulant 62 in a mold, and then heat the encapsulant 62 with the mold closed to perform post-cure, and then open the mold to remove the semiconductor device 1. The heating conditions for post-cure are, for example, a heating time of 160° C. or more and 190° C. or less, and a heating time of 2 hours or more and 8 hours or less. EXAMPLES
[0072] The effects of this embodiment will be described in more detail below with reference to examples, although the present invention is not limited to these examples.
[0073] 1. Preparation of the Composition The following raw materials were prepared as components of the composition. -Epoxy resin 1: pseudo-anthracene type epoxy resin, manufactured by Mitsubishi Chemical Corporation, product number YX8800UH. -Epoxy resin 2: Special multifunctional epoxy resin, manufactured by Printec Co., Ltd., product name TECHMORE VG3101L. -Kneaded material 1: A polyester thermoplastic elastomer (manufactured by Unitika Ltd., product number UE-3400, flow start temperature 40°C) and a phenolic compound (a compound with crystallinity, manufactured by Printec, product name TP-VG100, weight average molecular weight 1000 or less, melting point 230°C) are mixed in a mass ratio of 1:1 and kneaded at a heating temperature of 150°C. The flow start temperature of the kneaded material is 65°C. -Kneaded material 2: A kneaded material obtained by mixing a polybutadiene-based thermoplastic elastomer (manufactured by M-Tech Chemical Co., Ltd., product name PD Powder, flow start temperature 90°C) and a phenolic compound (a compound having crystallinity. Made by Printec Co., Ltd., product name TP-VG100. Weight average molecular weight 1000 or less, melting point 230°C) in a mass ratio of 1:1 and heating and kneading at a heating temperature of 150°C. The flow start temperature of the kneaded material is 93°C. -Kneaded material 3: A kneaded material obtained by mixing an acrylic thermoplastic elastomer (manufactured by Kuraray Co., Ltd., product number LA2140) and a phenolic compound (a compound having crystallinity. Made by Printec, product name TP-VG100. Weight average molecular weight 1000 or less, melting point 230°C) in a mass ratio of 1:1 and heating and kneading at 200°C. The flow start temperature of the kneaded material is 80°C. - Mixture 4: A mixture obtained by mixing a polyester thermoplastic elastomer (manufactured by Unitika Ltd., product number UE-3400, flow start temperature 40°C) and a phenol compound (a compound having crystallinity, manufactured by Honshu Chemical Industry Co., Ltd., product name BiSP-AP, weight average molecular weight 1000 or less, melting point 190°C) in a mass ratio of 1:1 and heating and kneading at a heating temperature of 150°C. The flow start temperature of the mixture is 62°C. -Kneaded material 5: A kneaded material obtained by mixing a polybutadiene-based thermoplastic elastomer (manufactured by M-Tech Chemical Co., Ltd., product name PD Powder, flow start temperature 90°C) and a phenolic compound (a compound having crystallinity, manufactured by Honshu Chemical Industry Co., Ltd., product name BiSP-AP, weight average molecular weight 1000 or less, melting point 190°C) in a mass ratio of 1:1 and heating and kneading at a heating temperature of 150°C. The flow start temperature of the kneaded material is 90°C. -Kneaded material 6: Acrylic thermoplastic elastomer (Kuraray Co., Ltd., product number LA2140) and phenol compound (crystalline compound. Honshu Chemical Industry Co., Ltd., product name BiSP-AP. Weight average molecular weight 1000 or less, melting point 190°C) are mixed in a mass ratio of 1:1 and kneaded at 200°C. The flow start temperature of the kneaded material is 80°C. -Phenol compound 1: A compound having crystallinity. Manufactured by Printec, product name TP-VG100. Weight average molecular weight of 1000 or less, melting point of 87°C. -Silicone elastomer: Dow Toray Industries, Inc., part number EP2601. -PMMA core-shell rubber: Mitsubishi Rayon Co., Ltd., part number J-5800. -PSQ powder: manufactured by Nikko Rika Corporation, part number MKN03. -Cure accelerator: 2PHZ, manufactured by Shikoku Kasei Co., Ltd. Coupling agent: N-phenyl-3-aminopropyltrimethoxysilane, Shin-Etsu Chemical Co., Ltd., product number KBM573. -Colorant: Carbon black, manufactured by Mitsubishi Chemical Corporation, product number MA600. - Release agent: Carnauba wax, manufactured by Dainichi Chemical Co., Ltd., product name Carnauba F-100 -Spherical fused silica: manufactured by Denki Kagaku Kogyo Co., Ltd., product number FB5SDC.
[0074] The raw materials were mixed according to the composition shown in the table, mixed for 10 minutes using a mixer, and then kneaded using a two-screw roll while heating at 110°C. The mixture was cooled and then pulverized. The powder thus obtained was compressed into tablets to obtain a tablet-shaped composition.
[0075] 2.Evaluation Test The compositions were subjected to the following evaluation tests, the results of which are shown in Table 1.
[0076] (1) Linear expansion coefficient A transfer molding machine (model number ETA-30D) manufactured by Shinto Metal Industries was used, and the injection pressure was 6.86 MPa (70 kg / cm 2 The composition was molded under the conditions of a mold temperature of 175°C and a holding time of 150 seconds, and then post-cured by heating at 175°C for 4 hours. As a result, a test piece with a diameter of 5 mm and a length of 20 mm was prepared.
[0077] The test specimen was heated in an air atmosphere at a heating rate of 5°C / min using a Thermo plus TMA8310 thermomechanical analyzer manufactured by Rigaku Corporation. During the heating process, the dimensions of the test specimen at 50°C and at 100°C were measured, and the linear expansion coefficient of the test specimen was calculated from the results.
[0078] (2) Flexural modulus The test specimens were prepared in the same manner as in the case of "(1) Linear expansion coefficient" above, except that the size of the test specimens was 10 mm x 85 mm x 4 mm.
[0079] A three-point bending test was performed on the test piece using an Instron universal material testing machine Model 5965, and the flexural modulus of the test piece was calculated from the resulting stress-strain curve.
[0080] (3) Stress index The stress index was calculated by multiplying the linear expansion coefficient obtained in the above test (1) Linear expansion coefficient by the bending modulus obtained in the test (2) Bending modulus. The smaller the stress index, the better the warpage of the encapsulant when molded onto a low linear expansion substrate such as a silicon wafer, a non-alkali glass wafer, or a 42 alloy.
[0081] (4) Warpage evaluation A 12-inch 775 μm dummy wafer was used as the dummy chip, and a TOWA Corporation compression molding machine, model CPM-1080, was used to create an encapsulant with a thickness of 400 μm to cover the dummy chip under conditions of a molding temperature of 130°C and a holding time of 600 seconds. A Nikon Corporation measuring microscope, model MM-800, was used to measure the amount of warping at eight points on the periphery of the encapsulant, with the center of the encapsulant as the reference, and the maximum amount of warping was used as the evaluation value for the warping.
[0082] (5) Average long diameter of dispersed phase Among the components of the composition, 20 g of the components (resin components) except the inorganic filler were mixed on a hot plate, and the hot plate was heated to 150° C. for 10 minutes to cure the composition, thereby obtaining a cured product. A slice was cut from the cured product, and the slice was stained with ruthenium to obtain a sample. The sample was observed at a magnification of 500 times with a scanning electron microscope to confirm the presence or absence of the matrix and the dispersed phase. As a result, the presence of the matrix and the dispersed phase was confirmed in Examples 1 to 6, and the presence of the matrix and the dispersed phase was not confirmed in Comparative Examples 1 to 4. The scanning electron microscope image obtained for Example 1 is shown in FIG. 2, the scanning electron microscope image obtained for Example 2 is shown in FIG. 3, and the scanning electron microscope image obtained for Example 3 is shown in FIG. 4. In addition, the average major axis of the dispersed phase was obtained from the images obtained using a scanning electron microscope. Specifically, the dimensions of the major axes of the images of 10 dispersed phases were measured, and the average value of the obtained values was taken as the average major axis of the dispersed phase.
[0083] (6) Fluidity (formability) In accordance with the EIMS T901 standard, the composition was molded using a transfer molding machine (model number MF-015, manufactured by Technomaru City Co., Ltd.) at a temperature of 170°C and an injection pressure of 7.0 MPa, and the flow length (unit: cm) was measured. If this value is 100 cm or more, it can be determined that the moldability is particularly good.
[0084] [Table 1] [Explanation of symbols]
[0085] 1 Semiconductor device 50 Semiconductor elements 62 Encapsulating material
Claims
1. Contains a resin component (A) and an inorganic filler (B), The resin component (A) contains a reactive compound (p), a reactive compound (q) having a weight average molecular weight of 1000 or less and having a thermosetting reactivity with the reactive compound (p), and a thermoplastic polymer (r), The reactive compound (p) contains an epoxy resin, The reactive compound (q) contains a crystalline phenol compound, The thermoplastic polymer (r) contains at least one thermoplastic elastomer selected from the group consisting of a polyester-based thermoplastic elastomer, a polybutadiene-based thermoplastic elastomer, and an acrylic-based thermoplastic elastomer, The reactive compound (p), a kneaded product (C) obtained by kneading the reactive compound (q) and the thermoplastic polymer (r), and the inorganic filler (B) are mixed, A cured product obtained by thermally curing the resin component (A) comprises a matrix containing the thermoplastic polymer (r) and a dispersed phase containing a reaction product of the reactive compound (p) and the reactive compound (q) dispersed in the matrix. Sealing resin composition.
2. The average major axis of the dispersed phase is 5 nm or more and 1000 nm or less. The encapsulating resin composition according to claim 1 .
3. A reactive compound (p), a kneaded product (C) obtained by kneading the reactive compound (p), a reactive compound (q) having a weight average molecular weight of 1000 or less and having thermosetting reactivity, and a thermoplastic polymer (r); and mixing an inorganic filler (B), The reactive compound (p) contains an epoxy resin, The reactive compound (q) contains a crystalline phenol compound, The thermoplastic polymer (r) contains at least one thermoplastic elastomer selected from the group consisting of polyester-based thermoplastic elastomers, polybutadiene-based thermoplastic elastomers, and acrylic-based thermoplastic elastomers. A method for producing an encapsulating resin composition.
4. A semiconductor element; and a sealing material that seals the semiconductor element. The encapsulant is a cured product of the encapsulating resin composition according to claim 1 or 2. Semiconductor device.
Citation Information
Patent Citations
Epoxy resin composition and its production
JP1987192422A
Sealing resin composition and its production
JP1988225618A
Production of epoxy resin composition for semiconductor sealing
JP1988230732A
Resin composition for sealing and production thereof
JP1988280722A
Resin composition for sealing semiconductor and semiconductor device using the same
JP2003165846A